Loss of methylation in CpG sites in the NF‐κB enhancer elements of inducible nitric oxide synthase is responsible for gene induction in human articular chondrocytes. Issue 3 (25th February 2013) - de Andrés, María C.; Imagawa, Kei; Hashimoto, Ko; Gonzalez, Antonio; Roach, Helmtrud I.; Goldring, Mary B.; Oreffo, Richard O. C.
Abstract Objective To investigate whether the abnormal expression of inducible nitric oxide synthase (iNOS) by osteoarthritic (OA) human chondrocytes is associated with changes in the DNA methylation status in the promoter and/or enhancer elements of iNOS. Methods Expression of iNOS was quantified by quantitative reverse transcriptase–polymerase chain reaction. The DNA methylation status of the iNOS promoter and enhancer regions was determined by bisulfite sequencing or pyrosequencing. The effect of CpG methylation on iNOS promoter and enhancer activities was determined using a CpG‐free luciferase vector and a CpG methyltransferase. Cotransfections with expression vectors encoding NF‐κB subunits were carried out to analyze iNOS promoter and enhancer activities in response to changes in methylation status. Results The 1, 000‐bp iNOS promoter has only 7 CpG sites, 6 of which were highly methylated in both control and OA samples. The CpG site at −289 and the sites in the starting coding region were largely unmethylated in both groups. The NF‐κB enhancer region at −5.8 kb was significantly demethylated in OA samples compared with control samples. This enhancer element was transactivated by cotransfection with the NF‐κB subunit p65, alone or together with p50. Critically, methylation treatment of the iNOS enhancer element significantly decreased its activity in a reporter assay. Conclusion These findings demonstrate the association between demethylation of specific NF‐κB–responsive enhancer elements and the activation of iNOS transactivation in human OA chondrocytes, consistent with the differences in methylation status observed in vivo in normal and human OA cartilage and, importantly, show association with the OA process.